Imaging predictors of response to cardiac resynchronization therapy: left ventricular work asymmetry by echocardiography and septal viability by cardiac magnetic resonance. (11th September 2020) - Aalen, John M; Donal, Erwan; Larsen, Camilla K; Duchenne, Jürgen; Lederlin, Mathieu; Cvijic, Marta; Hubert, Arnaud; Voros, Gabor; Leclercq, Christophe; Bogaert, Jan; Hopp, Einar; Fjeld, Jan Gunnar; et al.
Abstract: Aims : Left ventricular (LV) failure in left bundle branch block is caused by loss of septal function and compensatory hyperfunction of the LV lateral wall (LW) which stimulates adverse remodelling. This study investigates if septal and LW function measured as myocardial work, alone and combined with assessment of septal viability, identifies responders to cardiac resynchronization therapy (CRT). Methods and results : In a prospective multicentre study of 200 CRT recipients, myocardial work was measured by pressure-strain analysis and viability by cardiac magnetic resonance (CMR) imaging ( n = 125). CRT response was defined as ≥15% reduction in LV end-systolic volume after 6 months. Before CRT, septal work was markedly lower than LW work ( P < 0.0001), and the difference was largest in CRT responders ( P < 0.001). Work difference between septum and LW predicted CRT response with area under the curve (AUC) 0.77 (95% CI: 0.70–0.84) and was feasible in 98% of patients. In patients undergoing CMR, combining work difference and septal viability significantly increased AUC to 0.88 (95% CI: 0.81–0.95). This was superior to the predictive power of QRS morphology, QRS duration and the echocardiographic parameters septal flash, apical rocking, and systolic stretch index. Accuracy was similar for the subgroup of patients with QRS 120–150 ms as for the entire study group. Both work difference alone and work difference combined with septal viability predicted long-term survival without heart transplantation with hazard ratio 0.36 (95% CI: 0.18–0.74) and 0.21 (95% CI: 0.072–0.61), respectively. Conclusion: Assessment of myocardial work and septal viability identified CRT responders with high accuracy. Graphical Abstract: